P103 LIBMAN–SACKS ENDOCARDITIS AND FIBROELASTOMA IN ANTYPHOSPHOLIPIDIC SYNDROME: A RARE COEXISTANCE. (18th May 2022) - Piscitelli, L; Pedone, C; Perugini, E; Coutsoumbas, G; Corbo, P; Martin, S; Dal Passo, B; Dattolo, G; Casella, G
Abstract: Background: Libman–Sacks endocarditis (LSE) is the most common cardiac manifestation of the antiphospholipid antibody syndrome (APS), a systemic autoimmune disease characterized by the presence of arterial and venous thrombosis associated with the persistent presence of antiphospholipid antibodies (Sydney criteria). Cardioembolic events, mainly stroke, are important prognostic determinants of APS. Echocardiography, mostly transesophageal, is the main diagnostic tool to early identification and timely management of LSE. Case Summary: we report a case of 33–year–old man, with no cardiovascular risk factors. In the last few months, he had a myocardial infarction without obstructive coronary artery disease, a femoral venous thrombosis and a cryptogenic stroke. After clinical and laboratory workout he received diagnosis of primary APS and started an anticoagulation therapy with warfarin. 2D and 3D transesophageal echocardiogram performed after stroke showed two vegetations of the mitral valve. The first one appeared as granular mass, attached to ventricular and atrial surface of the posterior leaflet, measuring 16 x 5 mm. The second one was a smaller, mobile, pedunculated and more hyperechogenic mass apposed on the anterior leaflet. Mitral valve had mild to moderate regurgitation. The patient underwent surgical vegetation excision due to the high embolic risk. Resected specimens revealed sterile fibrinous and verrucous vegetations referable to LSE and a papillary fibroelastoma. Discussion: In this case we demonstrated a very rare coexistence of abacterial endocarditis and papillary fibroelastoma. We can assume a predisposing role of fibroelastoma by altering the morphology and structure of the mitral leaflets in LSE development.